An Analysis of Translation Method Used by College Students in Translating An Article - Susie Kusumayanthi; Tiara Fitria (English Journal Literacy Utama, 2020)
The aim of the study is to find out the type of translation method that the college students use most in translating a text from English into Indonesia, and challenges that the college students face in translating the material. The subject of this research takes place in one College in Cimahi. The participants of this study are 10 college students who will translate a text from English into Indonesian. The college students translation method in translating a text from English into Indonesian are the research object. The data collection techniques used in this study involved doing the test, and interview. This research reveals that (1) the students use Literal translation as the method in translating a descriptive text as the most used translation method is Literal Translation that reached 69.4% as there are 125 sentences that are indicated as the Literal Translation Method out of 180 sentences of total. (2) The challenges of students that face in translating a descriptive text goes to the lack of vocabulary.